The Application of Taguchi-WSM, Taguchi-WPM and Taguchi-WASPAS Multicriteria Methods to Optimize Downtime in a Production Process - Isaac Temitope Abiola; Sunday Ayoola Oke (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
In the industrial transformation of animal feed for chickens, downtime analysis is a crucial part of the plant's operations. Unfortunately, the literature on downtime analysis has a serious shortcoming; it fails to link downtime with Taguchi method’s optimization and ranking. To correct this deficiency, this paper proposes a new method that couples the Taguchi scheme with the weighted sum method (WSM), weighted product method (WPM) and weighted aggregated sum product assessment (WASPAS) method. A new model was developed to contain downtime factors, levels, orthogonal matrix, signal-to-noise proportions, normalisation indices, criteria weights and preference scores. The results of the Taguchi-WSM, Taguchi-WPM and Taguchi-WASPAS show that workstation 2 has the highest rankings of 0.8446, 8.9090 and 4.8770 for the Taguchi-WSM, Taguchi-WPM and Taguchi-WASPAS, respectively. Also, the lowest rankings of 0.1553, 6.7990 and 3.4800 were recorded for workstation 1 using the Taguchi-WSM, Taguchi-WPM and Taguchi-WASPAS methods, respectively. However, from literature reports, WASPAS has been associated with the best results compared to WSM and WPM. Hence, from the various results of prioritizing workstations 1 and 2, the results of the Taguchi-WASPAS method are recommended. This is the first time the downtime problem for animal feed processing equipment will be approached by a joint optimization and ranking with the Taguchi scheme, WSM, WPM and WASPAS multicriteria methods.